Adverse childhood experiences, psychological distress, and the role of locus of control - I. Behrens; B. Schmalbach; E. Brähler; V. Clemens; K. Petrowski; J. M. Fegert (Frontiers in Epidemiology, 2026)
Adverse childhood experiences (ACEs), including abuse, neglect, and household dysfunction, are prevalent and represent a major risk factor for psychological distress in adulthood. Although control-related constructs such as self-efficacy, mastery, and perceived control have been widely examined in this context, the role of locus of control (LoC) remains less well understood. The present study investigated the associations between ACEs, LoC, and psychological distress, and examined whether LoC mediates or moderates the relationship between ACE exposure and psychological distress. Data were drawn from a representative survey of the German general population [ N = 2,463; age range 16–96 years; female 1,237 female (50.2%)]. ACEs were assessed using the Adverse Childhood Experiences Questionnaire, psychological distress was measured with the Patient Health Questionnaire–4, and LoC was assessed with the Internal–External Locus of Control Short Scale–4. Structural equation modeling with robust diagonally weighted least squares estimation was applied. Higher ACE exposure significantly predicted greater psychological distress and a more external LoC orientation. Mediation analyses indicated that LoC accounted for approximately half of the association between ACE exposure and psychological distress. In contrast, moderation analyses did not reveal a significant interaction effect between ACE exposure and LoC in predicting psychological distress. These findings highlight control beliefs as an important psychological factor, linking early adversity to adult psychological distress and suggest that interventions targeting perceived control may help mitigate long-term mental health consequences of childhood adversity.